Kontribusi Hardiness dan Psychological Capital terhadap Work Engagement pada Angota Dewan Kabupaten Tasikmalaya - R. Diesa Yulisyanti Galena Mustarie; Endah Andriani Pratiwi (Humanitas (Jurnal Psikologi), 2024)
This research aims to find out how much Hardiness and Psychological Capital contribute on Work Engagement among Members of the Regional Legislative Council in Tasikmalaya. The research method used is a quantitative with a deductive approach. The sampling technique used saturated sampling technique, involving 50 members of the Regional Legislative Council Tasikmalaya. The instruments used include the OHQ with a Cronbach's alpha value of 0.930, the PCQ with a Cronbach's alpha value of 0.969, and the UWES-17 with a Cronbach's alpha value of 0.948. The research results show that Hardiness contributes to Work Engagement by 33.2%, there is a contribution of Psychological Capital to Work Engagement of 53.3%, and there is a simultaneous contribution of Hardiness and Psychological Capital to Work Engagement of 54.4%. Overall, the majority of scores for Hardiness (54%), Psychological Capital (48%), and Work Engagement (58%) were in the moderate category. Suggestions for future research include employing different methods such as a mixed-method approach.